The puzzle of non-western democracy - Youngs, Richard, 1968- (Carnegie Endowment for International Peace, 2015)
Western democracy is being questioned around the world. At the same time, Western aid groups are quick to say that they are not trying to impose a particular style of democracy on others and that they are open to supporting local, alternative forms of democracy. This book examines what it is about Western democracy that non-Westerners are reacting negatively to and whether the critics often are equating a dislike for certain Western social or economic features with an aversion to of Western political systems. It also explores the current state of debate about alternative forms of democratic practice in different regions-Asia, Africa, the Middle East, and Latin America-and then puts forward ideas about how Western actors engaged in democracy support can do a better job of incorporating new thinking about alternative democratic forms into their efforts.